2001
DOI: 10.1002/jso.1089
|View full text |Cite
|
Sign up to set email alerts
|

Follow‐up of sentinel node negative breast cancer patients without axillary lymph node dissection

Abstract: Although the follow-up is very short, SN biopsy only in node-negative breast cancer patients had no negative impact on the axillary failure rate and resulted in negligible morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
33
0
5

Year Published

2002
2002
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(40 citation statements)
references
References 36 publications
2
33
0
5
Order By: Relevance
“…Eleven previous studies have shown that axillary lymph node recurrence in early-stage breast carcinoma is rare after SLND alone, ranging from 0% to 1.4% at 22-46 months after surgery (Table 3). 4,[7][8][9][10][11][12][13][14][15] The current study of nearly 700 patients provides additional evidence that axillary lymph node recurrences occur infrequently after SLND alone (Ͻ 1%), and all 4 of the axillary lymph node recurrences in the current study were amenable to further treatment. In SLND studies, including the current study, the axillary lymph node recurrence rate after SLND is comparable to or less than the axillary lymph node recurrence rate of 1-2.5% after ALND for early-stage breast carcinoma at a median interval of 2.6 years between axillary surgery and disease recurrence.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…Eleven previous studies have shown that axillary lymph node recurrence in early-stage breast carcinoma is rare after SLND alone, ranging from 0% to 1.4% at 22-46 months after surgery (Table 3). 4,[7][8][9][10][11][12][13][14][15] The current study of nearly 700 patients provides additional evidence that axillary lymph node recurrences occur infrequently after SLND alone (Ͻ 1%), and all 4 of the axillary lymph node recurrences in the current study were amenable to further treatment. In SLND studies, including the current study, the axillary lymph node recurrence rate after SLND is comparable to or less than the axillary lymph node recurrence rate of 1-2.5% after ALND for early-stage breast carcinoma at a median interval of 2.6 years between axillary surgery and disease recurrence.…”
Section: Discussionmentioning
confidence: 54%
“…2,5 Furthermore, the side effects of SLND are negligible compared with the side effects of ALND. [3][4][5][7][8][9] However, the greatest concern with conducting SLND alone is the occurrence of a false-negative SLN biopsy. As a result, effective adjuvant therapy may not be offered and axillary metastases would be left untreated in the axilla, thus increasing the potential for axillary lymph node recurrence.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The long-term outcome of SLNB without ALND has not yet been evaluated and prospective randomised trials comparing SLNB alone vs SLNB plus ALND in SLN-negative patients as the American NSABP-B 32 trial or the European ALMANAC trial are in the recruitment phase. Few data exist on the local control of SLNB and there are only a few reports on SLNB alone without further ALND to date (Giuliano et al, 2000;Roumen et al, 2001;Schrenk et al, 2001;Chung et al, 2002). Axillary recurrences, as reported in those studies, range between 0 and 1.4% and follow-up periods range between 22 and 39 months.…”
Section: Discussionmentioning
confidence: 97%
“…Also, no lymphedema, insensibility, or decreased arm mobility (function) were noted. One case of seroma formation and 1 case of wound infection were also detected during follow up (8).…”
Section: Discussionmentioning
confidence: 93%